2011
DOI: 10.1029/2010jc006920
|View full text |Cite
|
Sign up to set email alerts
|

On the structure and dynamical features of intrusive layering in the Eurasian Basin in the Arctic Ocean

Abstract: Numerous conductivity‐temperature‐depth data obtained in the Arctic basins are analyzed to describe structural features of intrusive layering. Special attention is paid to large intrusions (vertical scale of 40–100 m) observed in upper, intermediate and deep layers (depth ranges of 150–200, 200–600 and 600–1000 m, respectively). The analysis of the intrusions is accompanied by descriptions of the frontal zones where the layering was observed. Based on observations detailed estimates of frontal zone parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 33 publications
0
46
0
7
Order By: Relevance
“…From the point of view of the author of this paper, a simple quasi-stationary (geostrophic) system of equations accurately describes the large-scale movement especially in the Arctic Ocean, where the influence of the β effect is not significant, the baroclinic fronts of large width in the ocean interior are often not intense (Kuzmina et al, 2011), and the N. Kuzmina: Generation of large-scale intrusions at baroclinic fronts baroclinic radius of deformation, H N/f , at H ∼ 100 m does not exceed 2-5 km (see also Sect. 3).…”
Section: Problem Formulation Derivation Of Basic Equation and Solutmentioning
confidence: 99%
See 4 more Smart Citations
“…From the point of view of the author of this paper, a simple quasi-stationary (geostrophic) system of equations accurately describes the large-scale movement especially in the Arctic Ocean, where the influence of the β effect is not significant, the baroclinic fronts of large width in the ocean interior are often not intense (Kuzmina et al, 2011), and the N. Kuzmina: Generation of large-scale intrusions at baroclinic fronts baroclinic radius of deformation, H N/f , at H ∼ 100 m does not exceed 2-5 km (see also Sect. 3).…”
Section: Problem Formulation Derivation Of Basic Equation and Solutmentioning
confidence: 99%
“…According to Kuzmina et al (2011), in the upper layer of the PDW where the large-scale intrusions are observed in the Eurasian Basin at stable-stable stratification, the following estimates of N, f , and β are typical: N ≈ 2 × 10 −3 s −1 , f = 1.4×10 −4 s −1 , and β < 0.3×10 −11 m −1 s −1 (at latitude of 83 • N and higher). Therefore, for disturbances, for example, with the vertical scale of H = 100 m, the Rossby radius of deformation is only H N/f ≈1 km.…”
Section: Application To Thermohaline Intrusions In the Eurasian Basinmentioning
confidence: 99%
See 3 more Smart Citations